An etchant for etching nickel-based single crystal high-temperature alloy, an etchant method, and a device for implementing the method

By using corrosion agents composed of H2O2 and HCl aqueous solutions with specific ratios, combined with magnetic stirring and cooling technology, the existing metallographic corrosion agents are solved, and the problem of high-efficiency and safe nickel-based single crystals is achieved. Corrosion effect of high temperature alloy.

CN115261862BActive Publication Date: 2025-02-25TSINGHUA UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211084996.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-06
Publication Date
2025-02-25
Estimated Expiration
2042-09-06

AI Technical Summary

Technical Problem

The existing metallographic corrosion agents are harmful to the human body, have poor corrosion effect, and are complex in operation, which affects the observation efficiency of nickel-based single crystal high-temperature alloy structure.

Method used

A corrosive agent containing H2O2 aqueous solution, HCl aqueous solution, CuSO4·5H2O, FeCl3, trinitrophenol and acetone is provided. It is formulated with a specific volume ratio and concentration, combined with magnetic stirring and refrigerant cooling to achieve high-efficiency corrosion.

Benefits of technology

This corrosive agent has little harm to the human body and has high corrosion efficiency. It can effectively corrode the interdendrite structure of nickel-based single-crystalline high-temperature alloys. It is suitable for tissue observation under optical microscopes and electron microscopes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115261862B_ABST
    Figure CN115261862B_ABST
Patent Text Reader

Abstract

The present invention relates to an etchant for corroding a nickel-based single crystal high temperature alloy, an etchant method, and a device for implementing the method. The etchant for corroding a nickel-based single crystal high temperature alloy of the present invention contains an H2O2 aqueous solution, an HCl aqueous solution, CuSO4·5H2O, FeCl3, trinitrophenol, and acetone. The present invention also provides a method for corroding a nickel-based single crystal high temperature alloy and a device for implementing the method, wherein the etchant of the present invention is used, and the device comprises a first container and a second container; wherein the first container is placed in the second container, the first container is used to load the etchant, and the second container is used to load the coolant. The etchant of the present invention has an excellent corrosion effect on the nickel-based single crystal high temperature alloy. The etchant of the present invention has high corrosion efficiency and low toxicity. Relying on the etchant method of the present invention and the device for implementing the method, the possibility of accidents can be reduced and the safety of workers or scientific researchers can be protected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an etchant for corroding nickel-based single crystal high-temperature alloy, a corrosion method and a device for implementing the method, and belongs to the field of material analysis. Background Art

[0002] Nickel-based single crystal superalloys can still maintain high toughness and strength at high temperatures, and are therefore widely used in the preparation of turbine blades for aircraft engines and heavy-duty gas turbines. After decades of development, nickel-based single crystal superalloys have evolved into multiple generations. At present, the most widely used superalloy in my country's high-performance aircraft engines and gas turbines is the second-generation nickel-based single crystal superalloy. Compared with the first-generation superalloys, the second-generation superalloys add the element Re for solid solution strengthening and to hinder dislocation movement in order to obtain better high-temperature mechanical properties.

[0003] The cast structure of nickel-based single crystal high-temperature alloy mainly includes dendrite structure and interdendritic structure. The dendrite structure is composed of a single γ phase, and the crystal structure is FCC crystal. The interdendritic structure is composed of γ phase and γ' phase, and the γ' phase structure is LI2 ordered phase. The second-generation nickel-based single crystal high-temperature alloy mainly contains a variety of elements such as Al, Co, Cr, Mo, W, Ta, Re, etc., among which Al, Ta, and Ti elements are segregated in the interdendritic structure, while Co, Cr, Re and W elements are segregated in the dendritic structure. Due to the different melting points of the segregated elements in the dendritic structure and the interdendritic structure, during the directional solidification process, the dendritic structure solidifies first to form a dendritic skeleton, and then the interdendritic structure is formed in the gaps of the dendritic structure.

[0004] In the metallographic structure observation of nickel-based single crystal high-temperature alloy, it is necessary to corrode one of the interdendritic structure or the dendrite trunk structure in order to observe the morphology of the solidified structure. The metallographic corrosive agent and the metal form an electrochemical reaction, and the reaction speed of different metallographic structures is different. In nickel-based single crystal high-temperature alloys, the corrosive agent generally corrodes the interdendritic structure first, and then corrodes the dendrite trunk structure. In nickel-based single crystal high-temperature alloys, the Al element segregated in the interdendritic structure will be passivated to form an oxide film during the corrosion process, which hinders the further progress of corrosion.

[0005] Common metallographic etchants include aqua regia, hydrofluoric acid-copper sulfate solution, and Carlin's reagent. Aqua regia, also known as "king's acid", is a mixture of nitric acid (HNO3) and hydrochloric acid (HCl) in a ratio of 1:3. At room temperature, aqua regia can corrode inert metals such as gold and platinum. Aqua regia has a very strong corrosive effect on the human body, and its corrosion intensity is higher than that of concentrated sulfuric acid, concentrated nitric acid, and concentrated hydrochloric acid. It is a very dangerous strong oxidizing and strong acidic corrosive liquid. Hydrofluoric acid-copper sulfate solution is made by mixing hydrogen fluoride and copper sulfate solution in a certain proportion (HF (20ml) + (2g) copper sulfate pentahydrate + water (100ml)). Hydrofluoric acid is not a strong acid, but due to the particularity of its fluoride ion structure, it has a very strong corrosiveness and can corrode materials that cannot be corroded by general corrosive agents, such as glass. Fluoride ions have a small radius and can enter the human body directly through the skin. Fluoride ions combine with calcium and magnesium ions in blood or tissues to form solid substances of calcium fluoride and magnesium fluoride, thereby blocking blood vessels and affecting the cardiovascular system and nervous system. Fluoride ions that enter the blood vessels can also combine with hemoglobin to form fluorohemoglobin, which inhibits the respiration of human cells and causes hypoxia. At the site of the burn, hydrogen fluoride can dissolve the cell membrane, causing tissue decay and dissolution. Carlin's reagent is made by mixing 2.5g of copper chloride dihydrate, 30ml of hydrochloric acid and 70ml of alcohol. Carlin's reagent is less corrosive to the human body than the other two corrosive agents mentioned above. However, at the same corrosion time, the corrosion depth of Carlin's reagent on the interdendritic tissue of the second-generation nickel-based single crystal high-temperature alloy is lower than that of the above two corrosive agents. When corroding large-sized tissues or deep corrosion, the corrosion time of Carlin's reagent is too long and the corrosion efficiency is too low.

[0006] Therefore, the above-mentioned corrosive agents either have one or more characteristics such as super acidity, oxidation or corrosion, and improper operation can easily cause irreversible damage to the human body and cause experimental accidents; or the corrosion effect is poor, the corrosion depth is shallow, and the corrosion time is long. These shortcomings affect the microstructure observation of the second-generation nickel-based single crystal high-temperature alloy. In order to improve the efficiency of metallographic microstructure observation and further ensure the safety of R&D personnel and operators, there is an urgent need for a type of metallographic corrosive agent and corrosion method that is relatively less harmful to the human body, has a better corrosion effect, and has higher comprehensive performance. Summary of the invention

[0007] Problem that the invention aims to solve

[0008] In view of the above problems existing in the prior art, the present invention provides an etchant, an etchant method, and a device for implementing the method for etching nickel-based single crystal high temperature alloy. The etchant of the present invention has little harm to the human body and has excellent corrosion effect. The etchant method of the present invention has low toxicity and high corrosion efficiency. The device of the present invention is simple to operate, can effectively improve the corrosion efficiency, and maintain the uniformity of the corrosion process.

[0009] Solutions for solving problems

[0010] The present invention provides an etchant for etching a nickel-based single crystal high-temperature alloy, comprising an H2O2 aqueous solution, an HCl aqueous solution, CuSO4·5H2O, FeCl3, trinitrophenol and acetone.

[0011] The volume ratio of H2O2 aqueous solution to HCl aqueous solution is 2:3 to 3:2.

[0012] The mass concentration of H2O2 aqueous solution is 45-55%, and the mass concentration of HCl aqueous solution is 90-95%;

[0013] The mass volume ratio of CuSO4·5H2O to H2O2 aqueous solution is 4-8g:100ml;

[0014] The mass volume ratio of FeCl3 to H2O2 aqueous solution is 2-5g:100ml;

[0015] The mass volume ratio of trinitrophenol to H2O2 aqueous solution is 0.5-2g:100ml.

[0016] According to the etchant of the present invention, the volume ratio of acetone to H2O2 aqueous solution is 40-70:100.

[0017] The invention provides a method for etching a nickel-based single crystal high-temperature alloy, using the etching agent of the invention.

[0018] The corrosion method according to the present invention comprises the following steps:

[0019] Cleaning and polishing the nickel-based single crystal high-temperature alloy;

[0020] The cleaned and polished nickel-based single crystal high-temperature alloy is corroded by using the corrosive agent of the present invention.

[0021] According to the etching method of the present invention, the cleaned and polished nickel-based single crystal high-temperature alloy is cooled by a refrigerant while being corroded.

[0022] According to the corrosion method of the present invention, during the cooling process, the temperature of the refrigerant is below 10°C.

[0023] According to the etching method of the present invention, magnetic stirring is performed while etching the cleaned and polished nickel-based single crystal high-temperature alloy.

[0024] The present invention also provides a device for implementing the corrosion method of the present invention, comprising a first container and a second container;

[0025] The first container is placed in the second container, the first container is used to load the corrosive agent, and the second container is used to load the coolant.

[0026] According to the device of the present invention, the device comprises a magnetic stirring part.

[0027] According to the device of the present invention, the second container has a temperature measuring portion.

[0028] Effects of the Invention

[0029] The corrosive agent of the present invention can effectively corrode the interdendritic structure of the cast state, and the metallographic structure after the corrosion by the corrosion method of the present invention can be applied to the observation of the dendritic structure under an optical microscope and an electron microscope. The corrosive agent and the corrosion method of the present invention are less harmful to the human body and have strong corrosion performance. Compared with traditional corrosive agents, the corrosive agent of the present invention has high corrosion efficiency and has certain universality for the second-generation high-temperature alloy.

[0030] The corrosion method of the present invention has low toxicity, and can reduce the possibility of accidents and protect the safety of workers or scientific researchers by relying on the corrosion method of the present invention. The corrosion method of the present invention has high corrosion efficiency and can quickly corrode the interdendritic structure in the second-generation nickel-based single crystal high-temperature alloy, thereby improving research efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Schematic diagram of the etching method of the present invention

[0032] Figure 2 Confocal microscopy results of sample-I of Example 1 of the present invention

[0033] Figure 3 Optical microscope observation results of sample-I of Example 1 of the present invention

[0034] Figure 4 Scanning electron microscope observation results of sample-I of Example 1 of the present invention

[0035] Figure 5 Scanning electron microscope observation results of sample of comparative example 1 of the present invention - comparison 1

[0036] Figure 6 Scanning electron microscope observation results of the sample of comparative example 2 of the present invention - pair II

[0037] Figure 7 Scanning electron microscope observation results of sample III of comparative example 3 of the present invention

[0038] Figure 8 Scanning electron microscope observation results of sample-II of Example 2 of the present invention

[0039] Fig. 9 Scanning electron microscope observation results of sample-III of Example 3 of the present invention

[0040] Fig.10 Scanning electron microscope observation results of sample-IV of Example 4 of the present invention

[0041] Fig.11 Scanning electron microscope observation results of sample-V of Example 5 of the present invention

[0042] Fig.12 Scanning electron microscope observation results of sample VI of Example 6 of the present invention DETAILED DESCRIPTION

[0043] The following is a detailed description of the present invention. The following description of the technical features is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:

[0044] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints A and B.

[0045] In this specification, unless otherwise specified, the word "multiple" in "multiple", "multiple", "plurality", etc. means a numerical value of 2 or more.

[0046] In the present specification, the term “substantially”, “substantially” or “essentially” means that the error is less than 5%, less than 3% or less than 1% compared with the relevant perfect standard or theoretical standard.

[0047] In this specification, unless otherwise specified, "%" means mass percentage.

[0048] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0049] In the present specification, "optional" or "optionally" means that the event or situation described below may or may not occur, and the description includes cases where the event occurs and cases where it does not occur.

[0050] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0051] [Invention of the first aspect]

[0052] The present invention provides an etchant for etching a nickel-based single crystal high-temperature alloy, comprising an H2O2 aqueous solution, an HCl aqueous solution, CuSO4·5H2O, FeCl3, trinitrophenol and acetone.

[0053] Wherein, the volume ratio of H2O2 aqueous solution to HCl aqueous solution is 2:3 to 3:2;

[0054] The mass concentration of H2O2 aqueous solution is 40-50%, and the mass concentration of HCl aqueous solution is 90-95%;

[0055] The mass volume ratio of CuSO4·5H2O to H2O2 aqueous solution is 4-8g:100ml;

[0056] The mass volume ratio of FeCl3 to H2O2 aqueous solution is 2-5g:100ml;

[0057] The mass volume ratio of trinitrophenol to H2O2 aqueous solution is 0.5-2g:100ml.

[0058] According to the etchant of the present invention, the volume ratio of acetone to the H2O2 aqueous solution is 40-70:100.

[0059] H2O2, HCl, CuSO4·5H2O, and FeCl3 can cooperate with each other to make the solution more corrosive to the interdendritic structure. The role of acetone is to volatilize and absorb heat, control the reaction temperature, and dissolve picric acid and organic impurities that may be produced during the corrosion process.

[0060] [Invention of the Second Aspect]

[0061] The present invention also provides a method for etching a nickel-based single crystal high temperature alloy, using the etchant of the present invention, wherein the nickel-based single crystal high temperature alloy is preferably a second generation nickel-based single crystal high temperature alloy.

[0062]

Cleaning and polishing

[0063] The etching method according to the present invention comprises the following steps: cleaning and polishing the nickel-based single crystal high-temperature alloy;

[0064] There is no particular limitation on cleaning and polishing. For example, preferably, the nickel-based single crystal high-temperature sample to be corroded is placed in an ultrasonic cleaning machine for ultrasonic cleaning.

[0065] Ultrasonic cleaning is carried out in two steps. In the first cleaning, the cleaning liquid of the ultrasonic cleaning machine is ultrapure water, which is used to clean and remove water-soluble impurities. In the second cleaning, the cleaning liquid of the ultrasonic cleaning machine is an organic solvent, which is used to clean and remove organic impurities. The organic solvent is preferably at least one of acetone, ethanol, and xylene, all of which have a good cleaning effect on nickel-based single crystal high-temperature samples. Acetone is particularly preferred. The ultrasonic cleaning frequency is 5MHz-100MHz, preferably 35MHz-70MHz. The cleaning time is 5 minutes-10 minutes, preferably 6-8 minutes. The cleaning time should not be less than 5 minutes, otherwise the attached impurities are not completely removed; the cleaning time should not be higher than 10 minutes, otherwise the organic solvent temperature is too high and volatilization is serious, resulting in reduced cleaning efficiency and causing organic matter to permeate the air. The cleaning temperature is 10℃-30℃, preferably 20℃.

[0066] After cleaning, the cleaned nickel-based single crystal high-temperature sample is mounted using a sample mounting machine, and the cleaned sample is further polished by manual polishing or automatic polishing machine. Preferably, the sample is polished using 180 mesh, 320 mesh, 600 mesh, 1000 mesh, 1500 mesh, 2000 mesh and 2500 mesh sandpaper in sequence until the sample has no obvious scratches.

[0067] The polished sample is polished, preferably, 9 micron diamond polishing liquid, 6 micron diamond polishing liquid, 3 micron diamond polishing liquid, 1 micron diamond polishing liquid, 0.25 micron diamond polishing liquid and 0.1 micron diamond polishing liquid are used in sequence to polish the sample. Each polishing time is more than 5 minutes. The polished sample is cleaned again as described above to remove attached impurities.

[0068]

corrosion

[0069] The cleaned and polished nickel-based single crystal high-temperature alloy is corroded by using the corrosive agent of the present invention.

[0070] According to the etching method of the present invention, the cleaned and polished nickel-based single crystal high-temperature alloy is cooled by a refrigerant while being etched. Preferably, during the cooling process, the temperature of the refrigerant is below 10°C.

[0071] During the corrosion process, a certain amount of heat will be generated. Therefore, a refrigerant is preferably used for reaction cooling. Preferably, the refrigerant is composed of water, glycerol, (NH4)2SO4 and Ba(NO3)2, and the ratio is preferably:

[0072] Water: glycerol (volume ratio) is 1:1;

[0073] The mass volume ratio of the initial addition amount of (NH4)2SO4 and water is preferably: 1g:25ml, and the mass volume ratio of the initial addition amount of Ba(NO3)2 and water is preferably: 1g:25ml.

[0074] The role of glycerol is to prevent the refrigerant from freezing, and the role of water is to make the solute in the refrigerant react and continue to cool down. The temperature of water and glycerol is 7-15 degrees. The initial temperature of the refrigerant should not be too low, which will cause the solute to freeze; nor should it be too high, otherwise the refrigeration effect will be poor. The dosage of (NH4)2SO4 and Ba(NO3)2 can be dynamically adjusted according to the number and size of the corrosion samples. During the corrosion process, they are continuously added according to the temperature to control the refrigerant temperature below 10°C, preferably above 4°C.

[0075] According to the etching method of the present invention, magnetic stirring is performed while etching the cleaned and polished nickel-based single crystal high-temperature alloy. During the etching process, three-dimensional microscopic depressions will be generated on the sample surface, such as Figure 2 As shown. As the reaction proceeds, the concentration of the corrosive liquid retained in the depression gradually decreases, and the corrosion efficiency decreases. Magnetic stirring allows the corrosive liquid to continuously corrode the depression, timely fill the corrosive solute in the depression, and accelerate the reaction. The magnetic stirring speed is 500-1000 rpm, and under high-speed rotation, the liquid surface needs to cover the sample at all times. If the speed is too low, the corrosion efficiency is low; if the speed is too high, it is easy to cause the corrosive liquid to leak.

[0076] The corrosion time of the corrosion method of the present invention varies according to the corrosion depth required for the experiment and the sample size. For example, for a second-generation nickel-based single crystal high-temperature alloy with a length, width and height of 1 cm, for optical microscope observation, the corrosion time is preferably 5 seconds to 5 minutes, and more preferably 10 seconds to 3 minutes; for electron microscope observation, it is preferably 1 minute to 2 hours; for confocal microscope observation, it is preferably 10 minutes to 10 hours, and more preferably 20 minutes to 3 hours.

[0077] During the corrosion process, acidic gases such as HCl and chlorine will be volatilized or generated. It is preferred to use an alkaline solution to absorb the above gases, such as a NaOH solution, with a mass concentration of 20%-60%.

[0078] After the etching is completed, preferably, the cleaning and polishing steps of the present invention are repeated to remove the etching agent attached to the surface.

[0079] [Third invention]

[0080] The present invention also provides a device for implementing the corrosion method of the present invention, comprising a first container and a second container;

[0081] Wherein, the first container is placed in the second container, the first container is used to load the corrosive agent, and the second container is used to load the coolant. Figure 1 As shown, the first container is a beaker, and a larger beaker is nested outside the beaker as the second container. When in use, the liquid level of the coolant cannot exceed the liquid level of the corrosive agent to prevent the first container from floating.

[0082] According to the device of the present invention, the device comprises a magnetic stirring unit. Figure 1 As shown, the first container and the second container are placed on a magnetic stirrer.

[0083] According to the device of the present invention, the second container has a temperature measuring part, such as a thermometer.

[0084] Preferably, if Figure 1 As shown, there is a gas absorption part above the first container and the second container, which can accommodate a solution for absorbing acidic gas, for example, preferably a sponge, in which a certain amount of NaOH solution is absorbed. Preferably, the thickness of the sponge and the concentration of the NaOH solution can be dynamically changed with the time required for the corrosion experiment, the sample volume, the volume of the corrosion solution, etc. Preferably, the thickness of the sponge is more than 0.5 cm, and the mass concentration of the NaOH solution is more than 20%, more preferably more than 30%.

[0085] The sponge can be replaced at any time according to the corrosion time. Taking a sponge with a thickness of 1 cm as an example, the sponge can be replaced at an interval of ≤10 minutes. For thicker sponges, the replacement time interval can be longer.

[0086] Example

[0087] Preparation of alloy to be corroded

[0088] The second generation nickel-based single crystal high temperature alloy DD6 was selected as the alloy to be corroded, and the sample size was 10mm×10mm×5mm. The sample was ultrasonically cleaned twice, with ultrapure water and acetone as the cleaning agents, the ultrasonic frequency was 50MHz, and the cleaning time for both times was 6 minutes. The temperature of water and acetone was controlled at 20°C. The cleaned sample was further polished, and the samples were polished with 180 mesh, 320 mesh, 600 mesh, 1000 mesh, 1500 mesh, 2000 mesh and 2500 mesh sandpaper in sequence until there were no obvious scratches on the sample. The polished sample was polished, and the samples were polished with 9 micron diamond polishing liquid, 6 micron diamond polishing liquid, 3 micron diamond polishing liquid, 1 micron diamond polishing liquid, 0.25 micron diamond polishing liquid and 0.1 micron diamond polishing liquid in sequence. Each polishing time was more than 5 minutes. The polished sample was ultrasonically cleaned again to obtain the alloy to be corroded.

[0089] Example 1

[0090] like Figure 1 As shown, the alloy to be corroded (nickel-based single crystal high-temperature alloy DD5) is connected to the plastic bracket through a thin wire, and the length of the thin wire is controlled so that the sample is just at half the height of the liquid surface.

[0091] Use a 500ml beaker as the second container and put in the coolant. The refrigerant ratio is: 30ml water, 30ml glycerol (propylene glycol), 2g (NH4)2SO4 and 2g Ba(NO3)2. The temperature of water and glycerol is 10℃, and (NH4)2SO4 and 2g Ba(NO3)2 can be at room temperature. Pay attention to the coolant temperature in real time, add appropriate amount of (NH4)2SO4 and Ba(NO3)2 in time, and control the coolant temperature at 5℃.

[0092] Prepare the corrosive agent, the corrosive agent ratio is: 80ml H2O2 (50% mass concentration aqueous solution), 80ml HCl (90% mass concentration aqueous solution), 4g CuSO4·5H2O, 2.4g FeCl3, 0.8g picric acid (trinitrophenol), 80ml acetone. Use a 250ml large beaker as the first container, pour the corrosive agent, add a magnetic stirrer, and place the second container in the center of the first container. Place the current beaker (two) on the magnetic stirrer and start stirring at a stirring speed of 700 rpm. Place the sample to be corroded, and place sponges absorbed with 40% NaOH solution on the two beakers respectively, the sponge thickness is 1cm, and the corrosion time is 2 minutes to obtain sample-I.

[0093] Sample-I was used to observe the local surface morphology of the corroded sample by confocal microscopy, such as Figure 2 shown.

[0094] The corrosion results of sample-I were observed by optical microscope. Figure 3 shown.

[0095] The corrosion results of sample-I were observed by scanning electron microscope. Figure 4 shown.

[0096] It can be seen from Example 1 that the etchant and the corrosion method of the present invention have excellent corrosion performance, the tissue morphology can be clearly seen in various conventional tissue morphology characterization methods, and it is suitable for nickel-based single crystal high-temperature alloy tissue observation under optical microscope, scanning electron microscope and confocal microscope.

[0097] Comparative Example 1

[0098] Prepare a water regia solution corrosive agent, the corrosive agent ratio is: 60ml HNO3 (90% mass concentration aqueous solution) and 180ml HCl (90% mass concentration aqueous solution). The alloy to be corroded is bound by a thin wire and directly placed in the corrosive solution (without the above-mentioned corrosion device), and the corrosion time is 2 minutes to obtain sample-I.

[0099] The corrosion results were observed by scanning electron microscopy. Figure 5 shown.

[0100] Comparative Example 2

[0101] Prepare hydrofluoric acid-copper sulfate solution etchant, the etchant ratio is: 40ml HF (90% mass concentration aqueous solution), 4g CuSO4·5H2O, 200ml water. Tie the alloy to be corroded by fine wire and directly put it into the corrosive solution. The corrosion time is 2 minutes to obtain sample-pair II.

[0102] The corrosion results were observed by scanning electron microscopy. Figure 6 shown.

[0103] Comparative Example 3

[0104] Prepare the Carlin reagent etchant, the etchant ratio is: 72 ml of HCl (90% mass concentration aqueous solution), 168 ml of anhydrous alcohol, 6 g of CuSO4·2H2O. The alloy to be corroded is bound by a thin wire and directly placed in the corrosive solution. The corrosion time is 2 minutes to obtain sample-III.

[0105] The corrosion results were observed by scanning electron microscopy. Figure 7 shown.

[0106] according to Figure 4-Figure 7 It can be seen that compared with common metallographic etching agents and etching methods, the etching solution and etching method of the present invention have good corrosion performance.

[0107] Example 2

[0108] Except for replacing DD6 with DD5, etching was performed in the same manner as in Example 1 to obtain Sample-II.

[0109] The corrosion results were observed by scanning electron microscopy. Figure 8 shown.

[0110] The corrosion method using the corrosive agent of the present invention has excellent corrosion performance on both DD5 and DD6 grades of nickel-based single crystal high-temperature alloys, and has certain universality.

[0111] Example 3

[0112] Except that the content of CuSO4·5H2O in the etching solution in Example 1 was adjusted to 6 g, other components remained unchanged and etching was carried out in the same manner as in Example 1 to obtain Sample-III.

[0113] The corrosion results were observed by scanning electron microscopy. Fig. 9 shown.

[0114] Example 4

[0115] Except that the content of FeCl3 in the etching solution in Example 1 was adjusted to 4g, other components remained unchanged and etching was carried out in the same manner as in Example 1 to obtain Sample-IV.

[0116] The corrosion results were observed by scanning electron microscopy. Fig.10 shown.

[0117] Example 5

[0118] The same etching solution and etching method as in Example 1 were used with an etching time of 5 minutes to obtain Sample-V.

[0119] The corrosion results were observed by scanning electron microscopy. Fig.11 shown.

[0120] Example 6

[0121] The same etching solution and etching method as in Example 1 were used, the etching time was 60 minutes, and the sponge was replaced every 10 minutes to obtain Sample-VI.

[0122] The corrosion results were observed by scanning electron microscopy. Fig.12 As shown in the figure, as the corrosion time increases, the interdendritic structure is removed more thoroughly.

Claims

1. A method for corroding a nickel-based single crystal high-temperature alloy, characterized in that: The nickel-based single crystal high temperature alloy is corroded by an etchant, wherein the etchant is composed of an aqueous solution of H2O2, an aqueous solution of HCl, CuSO4·5H2O, FeCl3, trinitrophenol and acetone. The volume ratio of H2O2 aqueous solution to HCl aqueous solution is 2:3~3:

2. The mass concentration of H2O2 aqueous solution is 45-55%, and the mass concentration of HCl aqueous solution is 90-95%; The mass volume ratio of CuSO4·5H2O to H2O2 aqueous solution is 4-8g:100ml; The mass volume ratio of FeCl3 to H2O2 aqueous solution is 2-5g:100ml; The mass volume ratio of trinitrophenol to H2O2 aqueous solution is 0.5-2g:100ml; The volume ratio of acetone to H2O2 aqueous solution is 40-70:

100. The corrosion method comprises the following steps: Cleaning and polishing the nickel-based single crystal high-temperature alloy; The cleaned and polished nickel-based single crystal high-temperature alloy is corroded by the corrosive agent, and magnetic stirring and cooling by a refrigerant are performed during the corrosion. The refrigerant consists of water, glycerol, (NH4)2SO4 and Ba(NO3)2.

2. The etching method according to claim 1, characterized in that: During the cooling process, the temperature of the refrigerant is below 10°C.

3. A device for implementing the etching method according to claim 1 or 2, characterized in that: It includes a first container, a second container and a magnetic stirring part; The first container is placed in the second container, the first container is loaded with the corrosive agent, the second container is loaded with a refrigerant, and a gas absorption part is provided above the first container and the second container. The gas absorption unit contains a solution for absorbing acidic gas. The gas absorption part is a sponge.

4. The device according to claim 3, characterized in that The second container has a temperature measuring portion.

Citation Information

Patent Citations

  • Chemical pickling solution for removing surface oxide layer of high-temperature alloys containing elements Cr and Al and application of chemical pickling solution

    CN104451731A

  • Corrosive agent for metallographic detection of nickel-based alloy and corrosion method

    CN107385443A

  • Measurement method for nickel base single crystal superalloy blade orientation deviation angle

    CN109238107A

  • Evaluation method of high-temperature and long-term aging element segregation of nickel base single crystal alloy

    CN110031600A

  • Metallographic corrosive agent for nickel-based alloy, and using method

    CN111979547A